The Pmt2p-Mediated Protein O-Mannosylation Is Required for Morphogenesis, Adhesive Properties, Cell Wall Integrity and Full Virulence of Magnaporthe oryzae - Guo, Min; Tan, Leyong; Nie, Xiang; Zhu, Xiaolei; Pan, Yuemin; Gao, Zhimou (Frontiers in Microbiology, 2016)
Protein O-mannosylation is a type of O-glycosylation that is characterized by the addition of mannose residues to target proteins, and is initially catalyzed by evolutionarily conserved protein O-mannosyltransferases (PMTs). In this study, three members of PMT were identified in Magnaporthe oryzae, and the pathogenic roles of MoPmt2, a member of PMT2 subfamily, were analyzed. We found that MoPmt2 is a homolog of Saccharomyces cerevisiae Pmt2 and could complement yeast Pmt2 function in resistance to CFW. Quantitative RT–PCR revealed that MoPmt2 is highly expressed during conidiation, and targeted disruption of MoPmt2 resulted in defects in conidiation and conidia morphology. The MoPmt2 mutants also showed a distinct reduction in fungal growth, which was associated with severe alterations in hyphal polarity. In addition, we found that the MoPmt2 mutants severely reduced virulence on both rice plants and barley leaves. The subsequent examination revealed that the fungal adhesion, conidial germination, CWI and invasive hyphae growth in host cells are responsible for defects on appressorium mediated penetration, and thus attenuated the pathogenicity of MoPmt2 mutants. Taken together, our results suggest that protein O-mannosyltransferase MoPmt2 plays essential roles in fungal growth and development, and is required for the full pathogenicity of M. oryzae.